Precision Soil Moisture Monitoring With Passive Microwave L-Band UAS Mapping - Kyung Y. Kim; Ziyue Zhu; Runze Zhang; Bin Fang; Michael H. Cosh; Andrew L. Russ; Eryan Dai; Jack Elston; Maciej Stachura; Albin J. Gasiewski; Venkataraman Lakshmi (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Although satellite-based soil moisture products are useful at regional and global scales, they do not meet the needs of users who require high-resolution information for applications such as precision agriculture or catchment hydrologic modeling. The advent of uncrewed aerial systems (UASs) has opened new opportunities for bridging this need. We offer one of the very first validation studies on a dry-down event captured by a novel L-band radiometer onboard a Black Swift Technologies fixed-wing S2 UAS. A fallow cornfield at the Beltsville Agricultural Research Center was selected as a study area to validate volumetric soil moisture estimates in mid-April. By leveraging a comparable radiative transfer model to that of soil moisture active passive and soil moisture ocean salinity derived products, brightness temperature retrievals from this sensor are shown to successfully capture a week of dry-down poststorm event, as validated by HydraGO probe estimates (calibrated with gravimetric samples) and a nearby soil climate analysis network station. However, with a reported spatially averaged bias of −0.107 m3/m3 (compared to calibrated moisture values) and an ubRMSE of 0.028 m3/m3 potential concerns remain regarding the sensor calibration, vegetation and surface roughness corrections, and georeferencing. Nevertheless, given the potential of UAS for on-demand, high-resolution soil moisture retrievals, this collaborative effort provides critical feedback for informing future applications and improvements in the field of passive microwave remote sensing.